Giant spontaneous exchange bias effect in Sm1.5Ca0.5CoMnO6 perovskite. (21st March 2016) - Giri, S K; Sahoo, R C; Dasgupta, Papri; Poddar, A; Nath, T K
Abstract: We report here on the enormously large value of the spontaneous exchange bias (SEB) of 5.1 kOe in the Sm1.5 Ca0.5 CoMnO6 bulk double perovskite system after zero-field cooling from an unmagnetized state. Depending on the path used for measuring the magnetic hysteresis loop, P-type or N-type, the EB field varies significantly. Dc and ac magnetization reveals a super-spin-glass-like (SSG) state below 19 K. The EB effect has been observed below the glassy transition temperature. The conventional exchange bias (CEB) as well as the SEB increase with a decrease in temperature and show monotonic variation. All these interesting features can be explained through the multimagnetic phase of double perovskite and the onset of unidirectional anisotropy driven by interface exchange coupling between the SSG, turned isothermally into a field-induced superferromagnetic shell and antiferromagnetic core.